Impiana Home Design Sdn. Bhd. / Wan Rosmawati Wan Awang ... [et al.] - Wan Awang, Wan Rosmawati; Kadim, Siti Nor Aini; Wan Zakaria, Wan Ilyani; Jamen, Mohamad Hafiz; Wan Hassan, Wan Ahmad Wardi (Faculty of Civil Engineering, 2002)
The great British Prime Minister Winston Churchill said that we build our buildings and then they shape us. This is certainly of anyplace we spend time, but nowhere is it more truly than in the home. Home is the place where adults can release the pressure, children can learn honesty, integrity, dependability, and service to others by taking appropriates responsibility for the home, its maintenance, and the quality of life it provides. Home should be a place of refreshment and support, and it should be important to us as a place where the finest value can be espoused and reinforced.